Resistência de variedades de arroz (oryza sativa) ao ataque de sitophilus oryzae e sitophilus zeamays (coleoptera: curculionidae) - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
Agricultural products can be attacked by pests in the field and storage units. From the rice grains pests, the weevils Sitophilus oryzae (Linnaeus, 1763) and Sitophilus zeamays Motschulsky, 1855 (Coleoptera: Curculionidae) are the main ones, reducing the weight of the grains, causing commercial depreciation of the product, loss of nutritional value and germination strength, contamination by mites and funguses and so forth; because of these damages is practicable to seek varieties which are resistant to these insects. The experiments were conducted at the Agricultural Entomology Laboratory of the Federal Institute of Goiás -.Campus Urutaí, throughout the period from July 2013 through March 2014. The varieties of rice used were acquired at EMBRAPA Arroz e Feijão. The experimental design used was completely randomized with 22 varieties. The resistance of rice varieties to S. oryzae was evaluated in three storage periods at 30, 60 and 90 days after the storage of the grains, performing evaluations to determine the total of alive and dead insects and the grain’s mass reduction. For the S. zeamays were evaluated the varieties: average of emerged weevils, average mass of adults after 24 hours of emergency, average longevity of adults, average life cycle from egg through adult and average of dry mass for consumed grains. It also was analyzed the longevity of insects 35 days after the experiment installation. The data were subjected to variance analysis with the averages compared by the Skott Knott test at the probability of 5% using the statistical program SISVAR. The varieties Bonança, Esmeralda, Rio Verde and Sertaneja showed themselves resistant to rice weevil S. oryzae for causing death to the insect. The varieties Pepita and Progresso presented vulnerability to the rice weevil S. oryzae. The varieties Bonança, Cabaçú, Curinga, Esmeralda, IRGA 22, Monarca, Rio Verde, Sertaneja, Tangará and Vencedora showed resistance to S. zeamays for causing this insect’s death. The varieties Pepita, Soberana, Carisma, Progresso and Araguaia are susceptible to the S. zeamays due to the high number of emerged insects and higher consumption. The presence or absence of crack in the grains is an important morphological characteristic to manifest or not to the resistance in rice varieties.
Keywords: Armazenamento de grãos; Gorgulhos; Pragas do arroz.; Storage of grains; Weevils; Rice pests; CIENCIAS AGRARIAS